Perinatal Outcomes of High Risk Pregnancies: Experience of a Tertiary Care Hospital: Perinatal Outcomes in High Risk Pregnancies - Ghaffar, Saima; Channa, Shahla; Dars, Saira; Khan, Shafia; Liaquat, Farah; Shah, Hanozia (Pakistan Journal of Health Sciences, 2024)
High Risk Pregnancy (HRP) denotes a condition where the mother, the fetus, or both are predisposed to complications during the gestation period, at birth, or postnatally, which is affected by several factors. Objective: To analyze the perinatal outcomes of high-risk pregnancies, focusing on the experience of a tertiary care hospital. Methods: A longitudinal study over two years, from October 1, 2020, to December 31, 2022, was conducted on 213 high-risk pregnant women, via purposive sampling, who attended the antenatal clinic Liaquat University Hospital, Hyderabad and Jamshoro. After obtaining informed written consent, interviews were conducted with the participants to collect data about their sociodemographic, obstetric, and gynecological histories. Perinatal outcomes were evaluated on the 8th day post-delivery, during which details concerning maternal and fetal complications in terms of morbidity and mortality, were documented. Results: Rh-negative pregnancy was found to be the most high-risk factor with 24.4% (52) of the cases, followed by teenage pregnancy at 12.2% (26), and short stature at 10.9% (23). Additionally, severe anemia was found in 21 women (9.8%), Pregnancy Induced Hypertension (PIH) in 18 women (8.6%), and obesity was also seen in 18 women (8.6%). Other noted risk factors included grand multigravida in 13 women (6.1%), thyroid disorder 4.9% (10), twin pregnancy 3.7% (8) and congenital fetal anomaly, polyhydramnios, oligohydramnios each with 2.4% (5). Conclusions: This study significantly contributes to the body of knowledge on high-risk pregnancies and their outcomes.